Integrating Local Customs in Mini-Drama Project to Improve Speaking Confidence and Promote Contextual and Fun Learning for Multilingual and Multiethnic EFL Classes: What Do College Students Think? - Lalu Jaswadi Putera (Departement of Mathematics Education, 2023)
This research is aimed to ascertain the integration of local customs (indigeneous languages, traditional costumes, local folklores) of Sasambo communities in mini-drama activities for multilingual and multiethnic EFL classes to improve student’s speaking confidence and promote contextual and fun learning based on the students’ perspectives. This study investigated the students' perceptions on: (a) forming groups with mixed ethnic and language background members; (b) using traditional costumes in mini-drama performance; (c) theming the mini drama based on local Sasambo folklores; and (d) the students’ overall perception on integrating local customs in mini-drama project. Data of this survey research were collected through a questionnaire, interview, and classroom observations. A total of 238 first-semester students from various study programs at the University of Mataram were involved. The results show that the majority of students expressed positive and very positive views towards the integration of local cultures in mini-drama project. They responded positively to setting the group in mixed ethnic and language backgrounds to perform the mini-drama (96.2%), wearing traditional costumes for mini-drama performances (92%), theming mini-drama based on the local Sasambo folklores that translated into English (94.5%), and showing positive impacts of integrating local Sasambo customs (indigeneous languages, traditional costumes, local folklores) in a mini-drama project on improving the students’ speaking skill, confidence, and happiness (92.8%).